Neklinično preverjanje varnosti zdravil, namenjenih pediatrični populaciji - Klinc, Igor (Farmacevtski vestnik, 2022)
In the treatment of paediatric population, doctors are often prescribing medicines which were not registered for children. With such prescribing they take into account the differences in characteristics between adults and children. Such experimenting had some tragic consequences in history. With the change of the regulation within the European Union in the field of a new medicine registration procedure, it's since the year 2007 mandatory to prepare a paediatric investigation plan during the medicine development. Based on that the European medicines agency prepared Guidelines on the need for non-clinical testing in juvenile animals of pharmaceuticals for paediatric indications. Just recently a new harmonized guideline S11 was adopted, which was prepared by The International Council for harmonisation. This paper summarizes the content of the S11 guidelines and the importance of drug testing for the paediatric population.
Keywords: juvenilne živali; neklinično preskušanje zdravil; pediatrična populacija; Pediatrija; registracija zdravil; smernica ICh S11; Zdravila; zdravstveni domovi